2020
DOI: 10.3390/ijerph17217802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Activity on Challenging Obesity in Pakistan: A Knowledge, Attitude, and Practice (KAP) Study

Abstract: Physical activity (PA) refers to any action produced by skeletal muscle that consumes energy. According to the World Health Organization (WHO), PA is the primary element that can improve health at the community level. Obviously, PA plays an important role in the social, physical, and mental development of men and women, as well as in balancing weight. However, the large-scale negative impacts of physical inactivity on health-related issues are also recognized globally, such as obesity, which is the source of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
2
26
3
Order By: Relevance
“…Although the participants had good knowledge and attitude levels, they demonstrated poor practice. Similar results were found in a study conducted by Laar et al 32 Alhawiti revealed similar obesity KAP results with satisfactory levels of knowledge but poor levels of attitude and practice. 23 However, another study showed that poor levels of obesity knowledge reflected poor attitudes and practice levels.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although the participants had good knowledge and attitude levels, they demonstrated poor practice. Similar results were found in a study conducted by Laar et al 32 Alhawiti revealed similar obesity KAP results with satisfactory levels of knowledge but poor levels of attitude and practice. 23 However, another study showed that poor levels of obesity knowledge reflected poor attitudes and practice levels.…”
Section: Discussionsupporting
confidence: 89%
“…23 KAP levels were significantly associated with BMI and WC; therefore, improving KAP levels by improving BMI and WC measurements could reduce obesity. 23 Laar et al 32 also found a significant correlation between knowledge and BMI. 32 Similarly, Saleh et al demonstrated that practice levels were significantly associated with BMI.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Physical activity refers to the action that consumes energy and produces skeletal muscle. It is the prime element for the improvement of health [ 1 ]. It has a considerable role in fat loss and healthy weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…For the global population, BMI ranging from 18.5 to 24.9 is considered normal whereas BMI ranging from 25-29.9 means over-weight, 30-34.9 is obesity class I, 35-39.9 is obesity class II and > 40 is obesity class III. Normal BMI ranges from 18.5 to less than 23 in South Asian countries, 23-27.5 is labeled over-weight and 27.5-32.5, 32.5-37.5, and above 37.5 are obesity class I, II, and III [ 1 ].…”
Section: Introductionmentioning
confidence: 99%